2018
DOI: 10.1136/bmjopen-2017-021445
|View full text |Cite
|
Sign up to set email alerts
|

Contextual characteristics associated with the perceived neighbourhood scale in a cross-sectional study in a large urban centre in Brazil

Abstract: IntroductionHealth outcomes have been associated with physical and social characteristics of neighbourhoods, but little is known about the relationship between contextual factors and perceived neighbourhood scale.ObjectiveTo identify the contextual factors associated with self-perceived neighbourhood scale.MethodsWe analysed data from a cross-sectional population-based study in Belo Horizonte, Brazil, that took place in 2008–2009. The dependent variable was perceived neighbourhood, encoded as an ordinal scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Entretanto, por ser uma área pequena, o setor censitário é capaz de refletir o ambiente do bairro no qual o indivíduo está inserido. 48 Os dados utilizados foram do ano de 2019, então não foram analisadas as mudanças que ocorreram após a pandemia de Covid-19. 49 Por fim, ao avaliar a distância física a ser caminhada entre os estabelecimentos de alimentos e os centroides dos setores censitários, não foram consideradas as dificuldades que podem ser encontradas, como aclives, declives, iluminação, presença de calçamento e questões de segurança.…”
Section: Discussionunclassified
“…Entretanto, por ser uma área pequena, o setor censitário é capaz de refletir o ambiente do bairro no qual o indivíduo está inserido. 48 Os dados utilizados foram do ano de 2019, então não foram analisadas as mudanças que ocorreram após a pandemia de Covid-19. 49 Por fim, ao avaliar a distância física a ser caminhada entre os estabelecimentos de alimentos e os centroides dos setores censitários, não foram consideradas as dificuldades que podem ser encontradas, como aclives, declives, iluminação, presença de calçamento e questões de segurança.…”
Section: Discussionunclassified
“…An example of a study that used this data collection procedure is Oropesa [29]. Other similar studies beyond the scope of our search (due to our restriction to English language publications) include de Almeida Célio, de Lima Friche [30] and Andrade, Peixoto [31].…”
Section: Methodsmentioning
confidence: 99%
“…Then, around each point representing a residence, circular buffers of the Euclidean type measuring 200 meters in radius were drawn. The 200-meter range was primarily chosen because the value was more recurrent, repeated in two different studies 12,15 ; secondly, because a study 21 using data also from the study "Saúde em Beagá" identified that for 57.8% of the participants, "neighborhood" was limited to the nearby houses until the end of the block. Within each buffer, establishments were counted by type.…”
Section: Exposure Variablesmentioning
confidence: 99%